To win the war is not the same as to ‘win the peace’: the coming constitutional moment in Ukraine - Kamiński, Antoni Z.; Kowalewska, Emilia (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2023)
Russia’s continuing aggression against Ukraine is exceptional both in terms of its scale and its global implications. A peaceful and prosperous future for Ukraine, neighbouring states and indeed the entire continent, depends upon two interrelated factors. The first is Ukraine’s ability to win, with Western support, the war initiated against it by the Russian Federation under Putin. This would bring about a new global opening, ending the Moscow-Beijing anti-Western axis in world politics. The second factor is Ukraine’s ability to take advantage of the constitutional moment that will present itself as attention shifts from the military effort toward the process of state reconstruction. Presenting the situation of Ukraine in regional, historical, and global context, we draw attention to specific challenges and choices that state elites will face post-war. We explain the internal and external implications of these choices to show why Ukraine should seize its upcoming constitutional moment. Drawing on both political theory and real world examples of constitutional revolutions, we explain the factors involved in the effective exploitation of the constitutional moment. We suggest that, channelled to constructive purposes, the demands and aspirations of Ukrainian citizens may help propel the political and economic reforms needed to secure social trust and a stable future. We conclude that multi-level political and civic engagement in a new constitutional process will be indispensable for reconstructing the institutional foundations for peace, democratic governance and the rule of law in post-conflict Ukraine.